International Conference on Al-Ghazali’s Legacy: Its Contemporary Relevance - ISTAC, ISTAC (Al-Shajarah Journal of the International Institute of Islamic Thought and Civilization (ISTAC), 2014)
International Conference on Al-Ghazali’s Legacy: Its Contemporary Relevance